Child rights and displacement in East Africa : agency and spatial justice in planning policy - Enns, Cherie C.; Kombe, Willibard J. (London ; New York, NY : Routledge, Taylor & Francis Group, 2023)
"Focusing on the intersection of spatial justice, child rights, and planning policy, this book investigates the challenges of resettlement in East Africa, where half of those displaced are children. Often the challenges created by displacement and resettlement are considered from an adult-centric perspective by planners and humanitarian and development experts. The spatial injustice of displacement and resettlement, the agency of children, and the application of tools such as Child Participatory Vulnerability Index (CPVI) is siloed, commonly overlooked, or discounted. This book uses a CPVI as well as a rights-based assessment of land-use policies, to investigate resettlement due to conflict and settlement in northern Uganda, floods due to climate change in Dar es Salaam, Tanzania, and urban to rural migration of children due to the aids pandemic in Western Kenya. Case studies are integrated from over a decade of field research with examples from applied planning projects and policy development in the East Africa region. This book uses spatial justice theory to show how child-friendly planning approaches can positively promote child rights in the context of resettlement. Providing important insights on how to enact more child-friendly planning in informal settlements, refugee camps, and displacement camps, this book will be of interest to planning and development professionals, and researchers across the fields of global development, planning, children's rights, and African studies"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Children's rights -- Africa, East